Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

The incorrect work of a student to solve an equation 2(y + 6) = 4y is shown below: Step 1: 2(y + 6) = 4y Step 2: 2y + 8 = 4y Step 3: 2y = 8 Step 4: y = 4 Which of the following explains how to correct Step 2 and shows the correct value of y? (5 points) a 2 should be distributed as 2y + 12; y = 6 b 2 should be distributed as 2y + 12; y = 3 c The equation should be y + 6 = 4y after division by 2; y = 2 d The equation should be y + 6 = 4y after division by 2; y = 1

Sagot :

Step-by-step explanation:

The wording is slightly confusing so I will just solve the equation.

2 (y + 6) = 4y

We expand the bracket

2y + 12 = 4y

We subtract 2y from both sides

12 = 2y

We divide both sides by 2

6 = y

Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.